Portable IoT Traffic Light System with Deterministic Cycle Recalculation and Real-Time Remote Configuration - Nada Tiyasa Salsabela; Tsania Camila Finnisa; Sendi Novianto (Jurnal Pendidikan Informatika (EDUMATIC), 2026)
Traffic control in temporary or emergency situations often requires portable traffic signal systems. However, many existing traffic light systems are designed as fixed infrastructure and limiting portability. This study proposes a portable IoT-based traffic light system with real-time remote configuration and a deterministic cycle recalculation mechanism to ensure coordinated signal operation. The system is implemented using ESP8266 microcontrollers, a web server with database integration, and WebSocket-based real-time communication. Performance evaluation measured synchronization accuracy and network communication quality using Round Trip Time (RTT), one-way delay, and Received Signal Strength Indicator (RSSI). The results show consistent cycle synchronization across all test scenarios, with no observed deviation between the expected and actual cycle durations. Outdoor communication testing demonstrated stable connectivity up to approximately 70 meters, with average RTT increasing from 33.44 ms to 95.44 ms while remaining within acceptable limits for real-time synchronization before degradation beyond 75 meters and connection loss at 80 meters. This study highlights the integration of portability, deterministic synchronization, and real-time configuration within a single system design. The proposed approach offers a flexible and cost-efficient alternative for temporary traffic management applications.